Analisa muzik dan persembahan dikir barat di Kelantan - satu penilaian dan persepsi masa hadapan - Shaipuddin Muhammad (Universiti Malaysia Kelantan, 2014)
Dikir barat performances are very famous performing arts in Kelantan. The community here is keeping the identity and culture since time immemorial yet. The influence of Bollywood music, especially rhythm, has a dikir barat songs are so getting a place in the hearts of fans of Kelantan. It survived and moved on each lip of the community here. Today, the influence and impact as well as new ideas began to spread at all players and especially pendikir chants songs. They make songs and chants of the song as a new medium to gain popularity, so they have a place among fans of the songs dikir barat. The impression these changes have led to an increase in offerings by local artists to hold among their offerings. Most of the local communities where they are happy to accept the changes muzik and offerings in the doxology song sung by a soloist versus group most discussions. The analysis in this study shows that the popularity of more lead to changes in the music and performances in which it affects the interests of listeners and viewers. Older people are more interested in the traditional performances. How they assess and view the changes in the music and performances of this western chant. It is hoped that the views and opinions that have been found to be able to rescue and preserve the art and culture of western chants from all corners of the continued demand by the people in Kelantan and Malaysia.